CLIMATE CHANGE DISCLOSURE AND FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIA’S PALM OIL INDUSTRY - Sugeng Riadi; Nanda Purwati; Mior Faizmie Yusof Za’Ba (Faculty of Economics and Business University of Mataram, 2026)
This study explores how climate change disclosures affect financial outcomes for palm oil firms in Indonesia. Drawing on secondary data from annual and sustainability reports of 23 listed companies over 2019-2023, we applied generalized least squares regression-both linear and quadratic (non-linear)-along with classical assumption tests. The findings reveal a significant linear link between climate change disclosure (CCD) and sales growth. However, CCD showed no meaningful impact on ROA or ROS in either model. These results suggest that such disclosures can build stakeholder trust and shape positive market perceptions, fueling sales growth-though they haven't yet translated to short-term profitability gains